3(x+9)=7(x-23)

Simple and best practice solution for 3(x+9)=7(x-23) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+9)=7(x-23) equation:


Simplifying
3(x + 9) = 7(x + -23)

Reorder the terms:
3(9 + x) = 7(x + -23)
(9 * 3 + x * 3) = 7(x + -23)
(27 + 3x) = 7(x + -23)

Reorder the terms:
27 + 3x = 7(-23 + x)
27 + 3x = (-23 * 7 + x * 7)
27 + 3x = (-161 + 7x)

Solving
27 + 3x = -161 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
27 + 3x + -7x = -161 + 7x + -7x

Combine like terms: 3x + -7x = -4x
27 + -4x = -161 + 7x + -7x

Combine like terms: 7x + -7x = 0
27 + -4x = -161 + 0
27 + -4x = -161

Add '-27' to each side of the equation.
27 + -27 + -4x = -161 + -27

Combine like terms: 27 + -27 = 0
0 + -4x = -161 + -27
-4x = -161 + -27

Combine like terms: -161 + -27 = -188
-4x = -188

Divide each side by '-4'.
x = 47

Simplifying
x = 47

See similar equations:

| 18a+31b+14a-2b= | | -5(2)+15=-10(7) | | x+2+x=-2 | | 6x-1(5x+5)=-8-2(x+12) | | 7-1/3 | | 6*9=n | | 6*8=n | | 5/4x-5/6x | | 3x+3=23-7x | | 3x+1/2(4x+8) | | 16x-6x-2x=0 | | 12(0)-6(3)=-18 | | 2x+(-2)*y=12 | | A*a=B*b | | 12(1)-6(5)=-18 | | 8s+2s=70 | | 6n-9=-62 | | 12(-2)-6(1)=-18 | | 6n-9=-57 | | factorx^4-8x^2+7=0 | | y/19=-5 | | -7k+9=56 | | 11.7x=46.8 | | -7k+9=49 | | -7k+9=44 | | 3-10k=26 | | 3-10k=13 | | 9-y=5x+3 | | 3-10k=10 | | 3-10k=5 | | 14-3n=4n | | 6y+2=88y-4 |

Equations solver categories